THE PROFILE AND PATIENT ACUTE HEPATITIS CHILDREN OUTPUT IN DR SOEBANDI JEMBER HOSPITAL - Adita Rini, Ika Wahyu; Shodikin, M. Ali (UNUSA Press, 2021)
Background: Indonesia is an endemic area for Hepatitis akut. District of Jember determines the status of extraordinary event Hepatitis akut at the end of 2019. The purpose of this study was the profile and patient acute hepatitis children output in dr Soebandi Jember Hospital in December 2019 until January 2020. Methods: This study was retrospective descriptive. The material was taken of the medical records Hepatitis akut patient at the pediatric departement of the dr. Soebandi Hospital in Jember. Results: In this study, patients most often occurred in male, age ranged between 7 – 14 years, and lived on the villages. The most common of clinical manifestation are anorexia, jaundice, fever, hepatomegaly, dark urine, vomiting and abdominal pain. The result of laboratory examination showed that Hepatitis acut patient had elevated of SGOT , SGPT, direct and total bilirubin. Conclusions: The combination of curcuma with SNMC (Stronger Neo-Minophagen C) reductly significant SGOT and SGPT serum levels (p < 0,001).